Development and validation of a liquid chromatography method for the simultaneous determination of alpha-tocopherol, retinol and retinyl esters in human serum using a monolithic column for the monitoring of anticancer therapy side effects - Urbánek, Lubor; Krcmová, Lenka; Solichová, Dagmar; Melichar, Bohuslav; Opletalová, Veronika; Solich, Petr (Journal of separation science, 2006)
Among other side effects, administration of anticancer agents is accompanied by manifestations of gastrointestinal toxicity and disturbances of antioxidant balance. The monitoring of these toxic effects in clinical practice is impeded by a dearth of reliable laboratory methods. Therefore, a simple and rapid reversed-phase high-performance liquid chromatography procedure for selective and sensitive determination of retinol, a-tocopherol, and retinyl esters (retinyl-palmitate and retinyl-stearate) in blood serum has been developed and presented in this study. A Series 200 LC HPLC instrument from Perkin Elmer (Norwalk, USA) with diode-array detector (DAD) was used for the analysis. Separations of retinol, alpha-tocopherol, retinyl-palmitate, and retinyl-stearate were performed using a Chromolith Performance RP-18e, 100 x 4.6 mm monolithic column from Merck (Darmstadt, Germany). Gradient elution was used at a flow rate of 3 mL/min; the mobile phase was methanol-water (95:5, v/v) for 0-2.1 min and methanol-2-propanol (60:40, v/v) for 2.1-4.9 min. The total time of analysis was 6 min. The injection volume was 20 microL and the analysis was performed at ambient temperature. Detection of retinol, alpha-tocopherol, and retinyl esters was carried out at 325, 295, and 330 nm, respectively. For practical assessment of the method, the vitamin A absorption test was performed on seven healthy controls as well as on six patients with non-small cell lung carcinoma or head and neck carcinoma previously treated by chemotherapy and/or radiotherapy, six patients with rectal carcinoma before chemoradiotherapy, four patients with gastrointestinal stromal tumor (GIST) before treatment with imatinib, and a breast cancer patient with chemotherapy-induced diarrhea. Present data demonstrate the feasibility of large scale HPLC determination of vitamin E, vitamin A, and retinyl esters in human serum using a silica monolithic column, and this method may represent a valuable aid in the laboratory monitoring of the toxicity of anticancer therapy.
Keywords: průjem; Chromatography, High Pressure Liquid; Drug Monitoring; alfa-tokoferol; Humans; pyrimidiny; Benzamides; imatinib mesylát; monitorování léčiv; absorpce; Imatinib Mesylate; Vitamin A; Antineoplastic Agents; Diarrhea; lidé; reprodukovatelnost výsledků; časové faktory; gastrointestinální stromální tumory; vitamin A; Esters; Gastrointestinal Stromal Tumors; Reproducibility of Results; Chromatography; piperaziny; chromatografie; protinádorové látky; benzamidy; alpha-Tocopherol; Piperazines; Absorption; Pyrimidines; Time Factors; kalibrace; vysokoúčinná kapalinová chromatografie; Calibration; estery